Analisis Biaya Satuan (Unit Cost) Dengan Metode Activity Based Costing (ABC) (Studi Kasus di Poli Mata RSD Balung Kabupaten Jember) - Anis Tri Sugiyarti; Nuryadi Nuryadi; Christyana Sandra (UPT Percetakan dan Penerbitan Universitas Jember, 2013)
Hospital is a government environment agency stablished to provide health services to the community. Therefore, hospitals desperately need input in the form of complete information, about is cost of a unit (unit cost). RSD Balung Jember that are required to perform the calculation of unit costs (unit cost) by of activity based costing (ABC) method. The purpose research is the calculation of unit costs (unit cost) by of activity based costing (ABC) method in Eyes at RSD Balung Jember. These research used descriptive with case study. Results sowed that, extraction corpus alienum Rp. 42.695; epilasi eyelash Rp. 36.579; incisi hordeolum or chalazion Rp. 41.956; tonometri Rp. 19.883; funduscopy Rp. 39.642; fluorosence Rp. 41.200; slyt lamp Rp. 14.119; visus Rp. 13.674; eye irrigation Rp. 60.544; extraction granuloma and ptyrigium Rp. 63.685; lift statches Rp. 36.507; anel test Rp. 60.288; prescription glasses Rp. 30.249; colour blind test Rp. 17.332; and health KIR Rp. 17.332;.The type of action that has a unit cost above tariff is funduscopy, fluorosence, lift stitches, anel test, and prescription glasses, while under the tariff is the extraction corpus alienum, epilasi eyelash, incisi hordeolum or chalazion, tonometri, slyt lamp, visus, eye irrigation, extraction granuloma and ptyrigium, color blind tests and health KIR. Keywords: Unit Cost, Activity Based Costing (ABC)